KAJIAN NATA DE OCHA SEBAGAI KONSUMSI PANGAN: EFEK PENAMBAHAN GULA DAN LAMA FERMENTASI TERHADAP KARAKTERISTIK NATA DE OCHA STUDY OF NATA DE OCHA AS A FOOD COMSUMPTION : EFFECTS OF SUGAR ADDITION AND FERMENTATION TIME ON THE CHARACTERISTIC OF NATA DE OCHA - Ummiyati, Anty; Kustyawati, Maria Erna; Satyajaya, Wisnu (Jurnal Agroindustri Berkelanjutan, 2024)
Nata de ocha produced from fermentation of kombucha is considered an innovative product to enhance its function for food consumption. Nata de ocha, a secondary metabolite product of sweet green tea kombucha fermentation using scoby starter, composes of cellulose produced during the fermentation. This study aimed to characterize nata de ocha production as affected by the sugar addition and fermentation time. The study arranged in a Complete Randomized Block Design factorially with 2 factors: sugar addition in the level of 0, 10, 15, and 20%; and fermentation time in the level of 0, 7, 14, and 21 days. The parameters measured were yield, thickness, total microbes, moisture, ash, and crude fibre content. The results showed that sugar addition and fermentation time significantly affected the yield and fibre content of nata de ocha. The high increase of yield (5.723%) and of crude fibre content (1.353%) was produced when the treatment was 15% sugar for 21days and for 144 days, respectively. It was concluded that nata de ocha may consider as food consumption; however, further research was needed for its possibility as an alternative of dietary fibre.